A design procedure for dual eccentrically braced-moment resisting frames in the framework of Eurocode 8. (1st January 2017) - Bosco, M.; Marino, E.M.; Rossi, P.P.
Highlights: The paper proposes a design procedure for dual eccentrically braced-moment resisting frames. The proposed procedure is consistent with Eurocode 8. The behaviour factor q for the determination of the seismic design force is provided. Dual and conventional EBFs are compared in terms of performance and structural weight. Abstract: Several research studies have proved the beneficial effects resulting from the presence of moment resisting frames and braced frames in dual structural systems. Nonetheless, Eurocode 8 provides design rules only for dual systems with moment resisting frames and concentrically braced frames and thus ignores that moment resisting frames may beneficially combine with other types of braced frames. In this paper, a design procedure for dual systems with moment resisting frames and eccentrically braced frames is proposed based on the current design provisions of Eurocode 8 for dual structures with moment resisting frames and concentrically braced frames. To evaluate the effectiveness of the proposed procedure, the seismic response of the designed systems is evaluated through incremental nonlinear dynamic analysis. The buildings considered are founded on hard or soft soil and are characterised by different values of the link length and number of storeys.